The artistic properties of rosewood (Dalbergia latifolia Roxb.) as a reference for the development of decorative veneers and synthetic vinyl. - Adik Bahanawan; Sudarmanto Sudarmanto; Imran Arra'd Sofianto; Wahyu Dwianto (Kementerian Perindustrian, 2022)
Research on the basic characteristics of sonokeling wood (Dalbergia latifolia Roxb.) has not been carried out widely. These properties include texture, pattern and color. This research aims to study and recognize these characteristics as a consideration of potential utilization of sonokeling wood to be developed widely. One simple technique in diversifying beauty of this wood was by drying treatment and visual photography technology combination. The research results showed that sonokeling wood had a very clear difference between heartwood and sapwood, and the growth rings are clearly visible. The wood texture is rather rough, especially at sapwood. The texture is rather smooth and shiny on heartwood. The pattern is very clear with beautiful black lines. The pattern is an embodiment of anatomical, chemical characteristics and radial section appearance of sawn wood. In production of decorative veneer, pattern will appear maximal in veneer slicing technique. Average color value (E) of sapwood = 63.54 (brown-yellowish brown) while heartwood = 32.28 (dark brown-blackish brown). Sonokeling wood is worthy to be widely developed considering of its beautiful patterns and colors, especially for product diversification of decorative veneers and synthetic vinyl. So that sonokeling wood become one of popular wood, especially in Java Island.